FISH analysis of selected soft tissue tumors: Diagnostic experience in a tertiary center. Issue 1 (28th May 2018) - Vargas, Ana Cristina; Selinger, Christina; Satgunaseelan, Laveniya; Cooper, Wendy A.; Gupta, Ruta; Stalley, Paul; Brown, Wendy; Soper, Judy; Schatz, Julie; Boyle, Richard; Thomas, David M.; Tattersall, Martin H.N.; et al.
Abstract: Aim: Fluorescence in situ hybridization (FISH) is an important ancillary tool for the classification of bone/soft tissue (BST) tumors. The aim of this study was to evaluate the contribution of FISH to the final classification of common BST entities in the molecular pathology department of the Royal Prince Alfred Hospital (RPAH), which is one of the most important referral centers for the management of sarcomas in Australia. Methods: All routine diagnostic FISH tests performed on BST formalin‐fixed paraffin embedded (FFPE) tissue specimens at the RPAH in a 5‐year period (February, 2010–November, 2015) were reviewed. FISH analyses presented in this study include commercial break‐apart probes ( SS18, FUS, DDIT3, FUS, USP6, PDGFB, TFE3 and ALK ) and a single enumeration ( MDM2 ) probe. Results: There were 434 interpretable FISH assays on BST samples including MDM2 ( n =180), SS18 ( n =97), FUS ( n =64), DDIT3 ( n =37), USP6 ( n =30), PDGFB ( n =13), TFE3 ( n =8) and ALK ( n =5). Discrepancies between the histopathological diagnosis and the FISH results were seen in 12% of the cases. In this subset of discordant cases, FISH contributed to the re‐classification of 7% of cases originally diagnosed as synovial sarcoma ( SS18 ) and 6% of adipocytic neoplasms ( MDM2 ) based on the presence or absence of the expected gene alteration. Conclusion: Our study confirms that paraffin FISH is a sensitive and specific ancillary tool in the diagnosis of BST neoplasms when used in the appropriate clinicopathological context. These findings highlight the need for further ancillary molecular tools in the diagnosis and characterization of challenging cases.